Clinical and Epidemiological Features of Diaphyseal Femoral Fractures In Douala - Leon Jules, Owona Manga; Tsigadigui, Jean Gustave; Chichom-Mefire, Alain; Ibrahima, Farikou; Félicité, Mbock Evelyne; Aurélien, Sosso Maurice (Journal of Medical Biomedical and Applied Sciences, 2018)
The femur, which is the strongest bone in humans, is often put under stressful constrains during the daily life trauma that can lead to consequences such as fractures.